ANALISIS KESULITAN MAHASISWA DALAM MENYELESAIKAN SOAL STATISTIK - Firdaus, Nizar (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2025)
Statistics can be interpreted as a method for working on and applying quantitative data to a number. This research was conducted in the 3rd semester class at the Islamic Center Islamic College, Demak Regency, Central Java Province in the Sharia Economics study program. For the questions given, there were 2 different questions but still looking for a normality test by students working according to the odd-numbered student ID number working on question number 1 and the even-numbered student ID number working on question number 2. The 3rd semester students at the Islamic Center Islamic College, Demak Regency, Central Java Province in the Sharia Economics study program as subjects in the study to be able to solve questions by manual calculation as previously stated before the implementation of ASTS first and then continued by comparing the results of the calculation with the help of the SPSS application, the subjects of the ASTS exam in this study